SEDEKAH BUMI DUSUN CISAMPIH (Studi kasus di Dusun Cisampih Desa Kutabima Kecamatan Cimanggu-Cilacap-Jawa Tengah) - abidin, zainal (El-HARAKAH (TERAKREDITASI), 2012)
Sedekah Bumi (earthâs alms) is an ethnic ritual to show their high regard to the earth as a place to live in. People depend on earth as it is a place where they do farming, get drink and food, and do other activities. For this reason, they feel that there should be any ceremony that shows their gratitude to the earth. Besides that, sedekah bumi also reflects thankfulness for peopleâs walfare and fortune and it is also believed to bring abundant crops. In Islamic perspective, the ritual of Sedekah Bumi accords to some Islamic principles, however, some ideas are also contradicted.